ULTRASOUND EVALUATION OF THE ARTERIAL ANASTOMOSIS FORMATION EFFECTIVE NESSIN THE EARLY POSTOPERATIVE PERIOD - Люлька, Є.М.; Оксак, Г.А.; Borkunov, A.L.; Люлька, О.М.; Ляховський, В.І. (World of Medicine and Biology, 2017)
The analysis of the medical records of 76 patients with symptoms of lower extremities critical ischemia (stage III-IV by the classification of Fontaine-Pokrovskiy) who underwent open reconstructive surgery on the arteries of femoral-popliteal and femoral-ankle segments for the atherosclerotic lesions of lower extremities arterieshas been performed. Patients were divided into 2 groups. The first group included 41 (53,9%) patients who underwent bypass surgery with the imposition of artificia / autovenous-arterial anastomosis "end-to-side" without determining the angle of sewing, the second - 35 (46,1%) patients who had the same anastomoses were imposed by the method developed by us, that included determination of the sewing angle and appropriate edges adaptation. To monitor the efficiency of reconstructive surgery all patients before surgery and 7-8 days after it conducted a color ultrasound of lower extremities arteries with the determination of ankle-brachial index, that allows to reliably determine the location, characteristics and length of occlusive-stenotic lesions of lower extremities arteries and distal arterial volume ability. It allows to determine indications for reconstructive surgery on the arteries of the lower extremities. After reconstructive surgery during ultrasound examination and ankle-brachial index determination of the affected lower limb was noticed significant improvement of blood flow parameters, especially in the patients of the second group. As a result of research efficacy of this diagnostic method was proved, thus it can be proposed to assess the quality of reconstructive surgery on the arteries of the lower extremities.